Multiplicative inequalities of Carlson type and interpolation - Larsson, Leo, 1972- (World Scientific, 2006)
This unique volume contains a selection of more than 80 of Yuval Ne'eman's papers, which represent his huge contribution to a large number of aspects of theoretical physics. The works span more than four decades, from unitary symmetry and quarks to questions of complexity in biological systems and evolution of scientific theories. In keeping with the major role, Ne'eman has played in theoretical physics over the last 40 years, a collaboration of very distinguished scientists enthusiastically took part in this volume. Their commentary supplies a clear framework and background for appreciating Yuval Ne'eman's significant discoveries and pioneering contributions.